Pencantuman Hak Opsi Perpanjangan Jangka Waktu Sewa Dalam Perjanjian Sewa Menyewa Rumah (Studi Kasus Putusan Pengadilan Negeri Denpasar Nomor 467/Pdt.G/2014/PN.Dps) - Jagat Krisno, Anak Agung Dalem; Sirtha, I Nyoman; Rudy, Dewa Gde (Acta Comitas : Jurnal Hukum Kenotariatan, 2018)
Indonesian Civil Code, Act Number 1 of 2011 and Government Regulations Number 14 of 2016 does not regulate firmly on the terms of the option rights. Whereas in practice, a lease agreement that includes an option lease term extension lease clause has generated a dispute between the parties in court. The formulation of the issues to be discussed in this thesis is 1). Is the Denpasar district court decision number 467 / Pdt.G2014 / PN.Dps in relation to the lease term extension option is in compliance with the principles of contract law? 2). What are the legal consequences of the extension of the lease term option in the lease agreement? The type of research in this thesis is normative legal research because it departs from the void norm in the Indonesian Civil Code, Act Number 1 of 2011 and Government Regulation Number 14 of 2016 is related to the option right to extend the lease term. The types of approaches used are legislation approach, legal concept analysis approach and case approach. Sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials is done by document study. The technique of analysis of legal materials used is technique description, evaluation, and argumentation. The results of research on the issues studied are the court ruling that overrides the tenant's option rights is incompatible with the principle of contract law, the principle of pacta sunt servanda, the principle of good faith and the principle of propierty. The tenant has the option to extend the lease term as stipulated in the lease agreement and the exercise of the right option is done in good faith.